2022
DOI: 10.1002/cssc.202200870
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur‐Decorated Ni−N−C Catalyst for Electrocatalytic CO2 Reduction with Near 100 % CO Selectivity

Abstract: Developing highly efficient electrocatalysts for electrochemical CO2 reduction (ECR) to value‐added products is important for CO2 conversion and utilization technologies. In this work, a sulfur‐doped Ni−N−C catalyst is fabricated through a facile ion‐adsorption and pyrolysis treatment. The resulting Ni−NS−C catalyst exhibits higher activity in ECR to CO than S‐free Ni−N−C, yielding a current density of 20.5 mA cm−2 under −0.80 V versus a reversible hydrogen electrode (vs. RHE) and a maximum CO faradaic efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…Yu and colleagues synthesized an S,N co-doped carbon black (CB) Ni single-atom catalyst. 206 The N,S-doped carbon black (Ni-NS-C) was obtained by adsorption of Ni 2+ with acid-activated CB, followed by pyrolysis with thiourea under an argon atmosphere at 800 °C for 1 h. The maximum FE CO of 99.7% was achieved for Ni-NS-C at a potential of 0.8 V RHE . Experiments and studies suggested that the introduction of S atoms in CB carriers caused the generation of more defects as well as a larger surface area.…”
Section: Optimization Strategy Of Sacsmentioning
confidence: 99%
“…Yu and colleagues synthesized an S,N co-doped carbon black (CB) Ni single-atom catalyst. 206 The N,S-doped carbon black (Ni-NS-C) was obtained by adsorption of Ni 2+ with acid-activated CB, followed by pyrolysis with thiourea under an argon atmosphere at 800 °C for 1 h. The maximum FE CO of 99.7% was achieved for Ni-NS-C at a potential of 0.8 V RHE . Experiments and studies suggested that the introduction of S atoms in CB carriers caused the generation of more defects as well as a larger surface area.…”
Section: Optimization Strategy Of Sacsmentioning
confidence: 99%
“…In an effort to further improve the CO 2 ‐to‐CO conversion on M−N−C catalysts, recent studies have also been dedicated to modifying the active sites (i. e., M‐N x ) with dopants, such as sulphur [97,98] . In this context, Lu et al [99] . obtained sulphur‐doped Ni−N−C catalyst via ion‐adsorption and pyrolysis treatment.…”
Section: M−n−c (M=fe Co or Ni) Catalysts For The Co2rrmentioning
confidence: 99%
“…Lu and co‐workers synthesized a S‐doped Ni−N−C catalyst (Ni‐NS−C) by a facile method, which achieved a very high CO 2 ‐to‐CO conversion efficiency of 99.7 % under −0.80 V vs. RHE. More importantly, their study revealed that the transition‐metal, Ni atoms, played as CO 2 ECR active sites, whereas S atoms improved its electrocatalytic activity synergistically by comparing these two S‐doped and S‐free catalysts [18] . These electrocatalytic CO 2 reduction reactions could also be boosted acquired by using the powerful strategy of sulfur activation in Fe‐NS−C, [19] Ni−S−C T [20] and so on.…”
Section: Introductionmentioning
confidence: 99%